Transactive energy systems in active distribution networks: a comprehensive review - Zou, Yunyang (2023)
Increasing penetration of distributed energy resources (DERs) introduced by different stakeholders, poses an immense challenge to power network operators. The traditional direct control of local DERs has the risk of violating preferences and privacies of stakeholders. A promising solution for supply-demand coordination is to utilize a transactive energy (TE) based energy management method to indirectly coordinate the local DERs, which enables the distribution-level energy providers, consumers, and prosumers to trade energy with each other through a transactive energy system (TES) trading platform. This paper provides a comprehensive review of a TES and presents a detailed classification from different perspectives, including TES participants, structure, commodity, clearing method, and solution algorithm. The presented detailed component-scale classification can be used as a reference for future TES designs. Finally, two additional market tools, i.e., penalty mechanism and loss allocation mechanism, are discussed as future focus areas, which can be seen as necessary complements to a TES for ensuring feasibility and fairness of energy trading.